Communication Apprehension Continuum in The New Normal: A Grounded Theory (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The study mainly focused on the experiences of the learners of Calamba Elementary School in Calamba City regarding communication apprehension. It utilized qualitative research with grounded theory as an approach. Through an in-depth individual interview, the learners' personal reflections of experience were recorded and analyzed to distinguish how they understand the effects of communication apprehension, as well as their coping mechanism to overcome it. Participants of this study were the 25 grade six learners from Calamba Elementary School who were chosen purposefully. In this study, the experiences of purposefully chosen participants were analyzed. The researcher used theoretical sampling and a two-cycle coding process to extract the themes and generate the theory. Results of the study revealed that the reasons for their communication apprehensions are the fear to be laughed at and afraid of bullying. It was found that some of the learners are nervous and shy, and they are afraid of their teachers which is why they seldom share their ideas, especially in front of the class. Meanwhile, CA affects the learners emotionally and socially. They experience emotional disturbance and social disparagement. The majority of the learners build a friendship to overcome communication apprehension. Also, it shows despite the challenges elementary learners are experiencing in communicating with others, they are not considering communication apprehension on thinking of leaving the school. Moreover, the teachers are also making ways to help learners who are afraid to share and express their ideas in front of the class. They are offering psychological assistance for the learners.